Architectural and construction discourse and genre features - Tolegenova, М.Ә.; Akimisheva, Ж.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article examines the formation of discourse as one of the directions of the anthropocentric paradigm in linguistics, based on the work of scholars who have defined discourse in terms of linguistics. On our part proposed the definition of the linguistic term architectural and construction discourse, which is the main object of research in this article, the subject of the research – its genre and structural features. Architectural and construction discourse, which is a complex discursive structure, denotes a set of texts focused on professional communication, considered in the architectural and construction field. We have indicated that the genre space of discourse is implemented within the framework of academic, scientific, project, legal, juridical, marketing and advertising discourse. We clarified that the architectural and construction discourse as far as information is conveyed is divided into oral and written, and speech genre is understood as thematic, substantive and structural unity. Types of speech genre of the architectural and construction sphere were defined: speech genre of academic discourse; speech genre of scientific discourse; speech genre of project and construction discourse; speech genre of legal discourse; speech genre of legislative discourse; speech genre of marketing discourse; speech genre of advertising discourse. The following parameters of the speech genre were singled out: the image of addresser and addressee, linguistic embodiment, communicative competence, communicative goal, communicative intention, dictum and modus content, combination of speech acts.